The importance of central auditory evaluation in Friedreich's ataxia - Zeigelboim, Bianca Simone; Teive, Hélio A. G.; Rosa, Michèlli Rodrigues da; Malisky, Jéssica Spricigo; Fonseca, Vinicius Ribas; Marques, Jair Mendes; Liberalesso, Paulo Breno (Arquivos de Neuro-Psiquiatria, 2018)
Objective To assess central auditory function in Friedreich's ataxia.Methods A cross-sectional, retrospective study was carried out. Thirty patients underwent the anamnesis, otorhinolaryngology examination, pure tone audiometry, acoustic immittance measures and brainstem auditory evoked potential (BAEP) assessments.Results The observed alterations were: 43.3% in the pure tone audiometry, bilateral in 36.7%; 56.6% in the BAEP test, bilateral in 50%; and 46.6% in the acoustic immittance test. There was a significant difference (p < 0.05) in the comparison between the tests performed.Conclusion In the audiological screening, there was a prevalence of the descending audiometric configuration at the frequency of 4kHz, and absence of the acoustic reflex at the same frequency. In the BAEP test, there was a prevalence of an increase of the latencies in waves I, III and V, and in the intervals of interpeaks I-III, I-V and III-V. In 13.3% of the patients, wave V was absent, and all waves were absent in 3.3% of patients.
Keywords: spinocerebellar degenerations; hearing disorders; Friedreich ataxia; evoked potentials, auditory; ataxic gait